Comparative Transcriptome Analysis Reveal Candidate Genes Potentially Involved in Regulation of Primocane Apex Rooting in Raspberry (Rubus spp.) - Liu, Jianfeng; Ming, Yuetong; Cheng, Yunqing; Zhang, Yuchu; Xing, Jiyang; Sun, Yuqi (Frontiers in Plant Science, 2017)
Raspberries (Rubus spp.) exhibit a unique rooting process that is initiated from the stem apex of primocane, conferring an unusual asexual mode of reproduction to this plant. However, the full complement of genes involved in this process has not been identified. To this end, the present study analyzed the transcriptomes of the Rubus primocane and floricane stem apex at three developmental stages by Digital Gene Expression profiling to identify genes that regulate rooting. Sequencing and de novo assembly yielded 26.82 Gb of nucleotides and 59,173 unigenes; 498, 7,346, 4,110, 7900, 9,397, and 4,776 differently expressed genes were identified in paired comparisons of SAF1 (floricane at developmental stage 1) vs. SAP1 (primocane at developmental stage 1), SAF2 vs. SAP2, SAF3 vs. SAP3, SAP1 vs. SAP2, SAP1 vs. SAP3, and SAP2 vs. SAP3, respectively. SAP1 maintains an extension growth pattern; SAP2 then exhibits growth arrest and vertical (downward) gravitropic deflection; and finally, short roots begin to form on the apex of SAP3. The Kyoto Encyclopedia of Genes and Genomes enrichment analysis of SAP1 vs. SAP2 revealed 12 pathways that were activated in response to shoot growth arrest and root differentiation, including circadian rhythm—plant (ko04712) and plant hormone signal transduction (ko04075). Our results indicate that genes related to circadian rhythm, ethylene and auxin signaling, shoot growth, and root development are potentially involved in the regulation of primocane apex rooting in Rubus. These findings provide a basis for elucidating the molecular mechanisms of primocane apex rooting in this economically valuable crop.